Kajian Kapasitas, Kebutuhan, Dan Efektivitas Parkir Di Bandar Udara El Tari Kupang - Amy Wadu; Harnen Sulistio; Achmad Wicaksono (Rekayasa Sipil, 2017)
Undisciplined and difficulty to find parking space are problems at El Tari Airport Kupang. The purpose of research to determine the capacity and demand of parking space and the effectiveness of parking services. The methods used include analysis of parking characteristics, linear regression, method of Importance Performance Analysis (IPA). The results showed that the demand parking space for car at El Tari Airport in existing condition is already exceeding capacity, while for motorcycle still sufficient. For the next 5 years the demand of parking space is 573 parking spaces (SRP) for cars and 599 SRP for motorcycles. The relationship between parking space demand and the number of passengers are y = 1.463x - 6203.6 for car and y = 3.3449x - 14565 for motorcycles. For parking service performance with IPA method, there are 7 variables as the main priority improvement, that is the ability of the parking operator to direct the vehicle to the parking lot, arrange the traffic in the parking area, direct the driver in and out of the parking lot, supervision of parking offenders, parking attendant behavior on the driver, circulation arrangement and vehicle parking position expressed by parking signs and markings, and parking patterns in order.